2012
DOI: 10.1111/j.1460-2466.2011.01624.x
|View full text |Cite
|
Sign up to set email alerts
|

When Good News Is Bad News: Explicating the Moderated Mediation Dynamic Behind the Reversed Mobilization Effect

Abstract: Recibido: 11 de diciembre de 2015 / Aceptado: 23 de junio de 2016 Resumen. El presente estudio pretende investigar acerca del efecto del enfoque (formato narrativo versus formato no narrativo) de las noticias sobre expulsión "en caliente" de inmigrantes en las actitudes hacia la inmigración. Concretamente, se persigue analizar el papel mediador de las emociones empáticas y el transporte narrativo, en el efecto provocado por las noticias en los participantes. Se trata de una investigación de naturaleza exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 64 publications
2
18
0
2
Order By: Relevance
“…B. Schuck & de Vreese 2012). Daher plädiert dieser Beitrag für eine Intensivierung der Positivitätsforschung in der Zukunft.…”
unclassified
“…B. Schuck & de Vreese 2012). Daher plädiert dieser Beitrag für eine Intensivierung der Positivitätsforschung in der Zukunft.…”
unclassified
“…Using a laboratory experiment, they found that negative tabloid news fosters support for referendums (Schuck and Vreese, 2008). Along similar lines, Schuck and de Vreese (2012) found that positive news framing tends to mobilise Eurosceptics to vote in referendums (Schuck and Vreese, 2012). In an earlier framing experiment, Vreese (2004) found that exposure to strategic news framing activates negative associations regarding EU enlargement, just as Vreese and Kandyla (2009) show that framing the EU Common Foreign and Security Policy (CFSP) in terms of either risk or opportunity significantly impacts on people's support for CFSP integration.…”
Section: State-of-the-art: the Use Of Experimentation In Eu Studiesmentioning
confidence: 91%
“…Cappella and Jamieson, 1997;Nelson et al, 1997;Price et al, 1997;de Vreese et al, 2006;Schuck and de Vreese, 2006). Cappella and Jamieson, 1997;Nelson et al, 1997;Price et al, 1997;de Vreese et al, 2006;Schuck and de Vreese, 2006).…”
Section: Framing European Enlargementmentioning
confidence: 99%
“…de Vreese, 2002de Vreese, , 2004Schuck and de Vreese, 2006;Maier and Rittberger, 2008). de Vreese, 2002de Vreese, , 2004Schuck and de Vreese, 2006;Maier and Rittberger, 2008).…”
Section: Framing European Enlargementunclassified